Onderscheiding der geesten in Marcus - H. Welzen (Acta Theologica)
In reading the gospel of Mark one gets the impression that one of the main activities of Jesus is exorcizing demons and unclean spirits. Exorcizing is part of the battle between powers inimical to God and the spirit of God that descended on Jesus when he was baptized by John. Unclean spirits deprive human beings of their identity, they dehumanize them and in the end they destroy them. Their uncleanness is the opposite of the holiness of God. It is possible to read the gospel of Mark as the struggle of Jesus with demons. His death and resurrection is the victory over their uncleanness. When it is said that a special kind of demons can be cast out only through prayer, this indicates the spirit of God who lives in the believers and who prays to God. It is by surrender to the will of God that unclean spirits are overcome.